Global Best Practices in Insurance Claim Cycle Time & Leakage - Kumar, Shishir (Assurances et gestion des risques / Insurance and Risk Management, 2010)
Insurers are losing huge amounts of money to fraudulent claims. To cope up with soaring claims, insurers are adopting the best claim practices to transform their operating model. However, they are still reluctant because their investment on technology should be justified with financial prudence. The study covers the best service practices and technologies implemented by various insurers during 2003-07. It reveals that majority of claim technologies have been implemented in the P&C segment. U.S. and UK accounted majority of the claim technology implemented. Insurers have been more focused towards claim administration & Processing globally. Aviva emerged as a leader in the claim technology implementation and deployment of radically innovated technologies.